Saphenous and Sciatic Nerve Blockade with and without Obturator Nerve Block for Tibial Plateau Levelling Osteotomy Surgery in Dogs: A Randomized Controlled Trial - Chiara Di Franco; Chiara Cipollini; Giacomo Figà Talamanca; Giulio Tazioli; Stefano Patroncini; Maurizio Calistri; Angela Briganti (Animals, 2023)
The objective of our study was to compare the efficacy of sciatic and saphenous ultrasound nerve blocks with and without US-guided obturator nerve block in dogs undergoing tibial-plateau-levelling-osteotomy (TPLO) surgery. This study was developed in two phases: identification of an ultrasound window in the inguinal region for obturator nerve block and utilization of it in dogs undergoing TPLO. Dogs were assigned randomly to one of two groups: one received the three blocks with 0.5% ropivacaine (ON group) and the second one (NoON group) with NaCl instead of ropivacaine for the obturator block. In phase 1, the obturator nerve was visible between the pectineus and the abductor muscles and was approached using an in-plane technique. It was possible to use the ultrasound window for phase two. The number of dogs that received at least one bolus of intraoperative rescue analgesia in the NoON group (12/15 dogs) was significantly higher (p = 0.003) in comparison with the ON group (4/15). An ultrasound window to block the obturator nerve in the inguinal compartment with an in-plane technique was found. The use of this approach could produce adequate analgesia with less motor function impairment in dogs for TPLO surgery.